The effect of two different crosslinkers on in vitro characteristics of ciprofloxacin-loaded chitosan implants - Esti Hendradi; Dewi Melani Hariyadi; Muhammad Faris Adrianto (Wolters Kluwer Medknow Publications, 2018)
The objective of this study was to determine and evaluate a controlled release implant of ciprofloxacin using bovine hydroxyapatite (BHA)-chitosan composite and glutaraldehyde or genipin as crosslinking agents. Ciprofloxacin implants were prepared using BHA, chitosan, ciprofloxacin at 30:60:10 and using three different concentrations of glutaraldehyde or genipin (0.3, 0.5, or 0.7%) as crosslinkers. Implants were formed as mini-tablet with 4.0 mm diameter weighing 100 mg using compression method. Further, the prepared ciprofloxacin implants were characterized for porosity, density, water absorption capacity, swelling, degradation, compressive strength, compatibility (Fourier transforms-infrared spectroscopy (FT-IR)), morphology (scanning electron microscope (SEM)), X-ray diffraction (X-RD), and in vitro drug release. The addition of glutaraldehyde or genipin as crosslinkers in ciprofloxacin implant showed controlled release profile of ciprofloxacin over a time period of 30 days. SEM photomicrograph revealed low porosity of the implant after crosslinking with glutaraldehyde or genipin. The FTIR study confirmed the formation of covalent imine bonds between chitosan and glutaraldehyde. Moreover, the addition of glutaraldehyde or genipin as crosslinkers caused a decrease in the mechanical strength of the implant. Increased concentration of glutaraldehyde or genipin reduced the crystallinity of BHA and chitosan, which were confirmed by X-RD studies. The results obtained from this study indicated that glutaraldehyde or genipin had the potential effect to retard ciprofloxacin release from BHA-chitosan-ciprofloxacin implant for 30 days.